Control of anthocyanin and non-flavonoid compounds by anthocyanin-regulating MYB and bHLH transcription factors in Nicotiana benthamiana leaves - Outchkourov, Nikolay S.; Carollo, Carlos A.; Gomez-Roldan, Victoria; de Vos, Ric C. H.; Bosch, Dirk; Hall, Robert D.; Beekwilder, Jules (Frontiers in Plant Science, 2014)
Coloration of plant organs such as fruit, leaves and flowers through anthocyanin production is governed by a combination of MYB and bHLH type transcription factors. In this study we introduced Rosea1 (ROS1, a MYB type) and Delila (DEL, a bHLH type), into Nicotiana benthamiana leaves by agroinfiltration. ROS1 and DEL form a pair of well-characterized transcription factors from Snapdragon (Antirrhinum majus), which specifically induce anthocyanin accumulation when expressed in tomato fruit. In N. benthamiana, robust induction of a single anthocyanin, delphinidin-3-rutinoside (D3R) was observed after expression of both ROS1 and DEL. Surprisingly in addition to D3R, a range of additional metabolites were also strongly and specifically up-regulated upon expression of ROS1 and DEL. Except for the D3R, these induced compounds were not derived from the flavonoid pathway. Most notable among these are nornicotine conjugates with butanoyl, hexanoyl and octanoyl hydrophobic moieties, and phenylpropanoid-polyamine conjugates such as caffeoyl-putrescine. The defensive properties of the induced molecules were addressed in bioassays using the tobacco specialist lepidopteran insect Manduca sexta. Our study showed that the effect of ROS1 and DEL expression in N. benthamiana leaves extends beyond the flavonoid pathway. Apparently the same transcription factor may regulate different secondary metabolite pathways in different plant species.